Jangle ki shahzadi - Zulfiqar Ahmed Tabish (Ferozsons (PVT) LTD Lahore, 2010)
Janglay Ki Shahzadi is an enchanting story of a princess who embarks on a daring adventure in the jungle, discovering hidden secrets and her own inner strength.